Relationship between H. pylori infection and some other risk factors in the incidence and recurrence of idiopathic nephrotic syndrome in children - Farrokh Farrokhnia; Ali Derakhshan; Mohammadhossein Fallahzade; Mitra Basiratnia (Babol University of Medical Sciences, 2023)
Background: Idiopathic nephrotic syndrome (INS) is one of the chronic diseases in children and it is important to identify its related factors. The present study aimed at investigating the relationship between H. pylori infection and the incidence and recurrence of idiopathic nephrotic syndrome in children. Methods: The total number of case participants was 40 and the total number of control participants was 41. Based on the number of cases of nephrotic syndrome (NS), the same number of healthy children of the same age and gender were selected as the control group. The information and data collected include demographic characteristics of patients, duration of disease, number of recurrences, blood pressure and blood excretion in urine, height, and weight, and presence of gastrointestinal symptoms on the checklist. The data were entered into SPSS and analyzed at a significance level of 05. Results: From 81 participants in the study, 11 (13.75%) cases were H. pylori positive, of whom 7 (17.5%) cases were in the control group and 4 (10%) cases were in the patients' group. There was no significant difference between the two groups in terms of H. pylori infection rate (P = 0.863). Moreover, there were no significant differences between the patients suffering from the nephrotic syndrome in terms of height, weight, blood pressure, hematuria, duration and recurrence of the disease (p>0.05). Conclusion: According to the evaluations performed in the present study, there was no relationship between low birth weight, blood pressure, disease duration, and disease recurrence with NS.